Usando el espacio : Análisis de estructura intrasitio y conductas de manufactura en la región subandina de Jujuy - Ortiz, Gabriela (2004)
Although there are important studies about the archaeology of the San Francisco valley, mainly those produced during the decade of 1970, we still know little about several aspects of the regional prehistoric occupations. Among these are the conducts regarding the use of space at different scales. The spatial distribution and characteristics of the surface artifacts collected and mapped at Aguas Negras site are analyzed using several structural indexes. This work shows how the study of the distribution of surface artifacts is meaningful to understand the organization of residential space.